Oral Intravascular Papillary Endothelial Hyperplasia Associated with an Organizing Thrombus: Case Report and Immunohistochemical Analysis - Darcy Fernandes; Daphine Caxias Travassos; Túlio Morandin Ferrisse; Elaine Maria Sgavioli Massucato; Cláudia Maria Navarro; Mirian Aparecida Onofre; Jorge Esquiche León; Andreia Bufalino (Hindawi Limited, 2016)
Intravascular papillary endothelial hyperplasia (IPEH) is a benign lesion of the skin and mucosa of vascular origin characterized by reactive proliferation of endothelial cells. A 76-year-old woman was referred presenting a painless nodule on the lip. Intraoral examination revealed bluish submucosal nodular proliferation, measuring 10 × 5 × 5 mm, affecting the lower labial mucosa. The lesion had a firm consistency and it was not fixed to the adjacent tissues. The main differential diagnoses were mucocele/mucus retention cyst, sialolith, or salivary gland neoplasia. An incisional biopsy was performed and during the intraoperative procedure an encapsulated red-bluish nodular mass was observed. Microscopic analysis revealed papillary endothelial proliferation in the center of the lesion and fibrin admixed with inflammatory cells in organization peripherally. There was no nuclear atypia, mitotic figures, or necrosis. The endothelial cells were CD34 positive, with low Ki-67 proliferation index (4%). α-SMA highlighted the vessel walls, whereas negativity for D2-40 excluded lymphatic origin. Final diagnosis was IPEH associated with an organizing thrombus. Dentists should be aware about this rare benign vascular lesion, whose final diagnosis is achieved only after histopathology analysis. Surgical removal is the treatment of choice and no recurrence is expected.